The complete mitochondrial genome and phylogenetic analysis of Tipula (Yamatotipula) nova Walker, 1848 (Diptera, Tipulidae) from Qingdao, Shandong, China - Zhao, Chuande (Mitochondrial DNA B Resour, 2019)
The genus Tipula Linnaeus, 1758 is a large group of crane flies with more than 2400 known species from 41 subgenera. In this study, we report the first complete mitochondrial (mt) genome sequence of the subgenus Tipula (Yamatotipula), which is a circular molecule of 15,668 bp with an AT content of 77.2%. The mt genome contains 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a long non-coding region. Three conserved overlapping regions, 8 bp between tRNA(Trp) and tRNA(Cys), 7 bp between ATP8 and ATP6, and 7 bp between ND4 and ND4L, are found. Phylogenetic analysis reveals that the Tipulomorpha includes the family Trichoceridae and the Trichoceridae is sister-group to the remaining Tipulomorpha.